2013
DOI: 10.1200/jco.2012.43.3912
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor–Resistant Disease

Abstract: A B S T R A C TPurpose EGFR-mutant lung cancer was first described as a new clinical entity in 2004. Here, we present an update on new controversies and conclusions regarding the disease. MethodsThis article reviews the clinical implications of EGFR mutations in lung cancer with a focus on epidermal growth factor receptor tyrosine kinase inhibitor resistance. ResultsThe discovery of EGFR mutations has altered the ways in which we consider and treat non-small-cell lung cancer (NSCLC). Patients whose metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
364
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 414 publications
(368 citation statements)
references
References 119 publications
2
364
0
2
Order By: Relevance
“…For example, resistance to molecular targeted therapies develops in most patients eventually. 5 In addition, alternative treatment modalities, other than cytotoxic chemotherapy, are needed for pulmonary adenocarcinoma patients without druggable molecular alterations. To solve these issues, other strategies for pulmonary adenocarcinoma need to be established, and recently cancer immunotherapy has emerged as a promising therapeutic strategy.…”
mentioning
confidence: 99%
“…For example, resistance to molecular targeted therapies develops in most patients eventually. 5 In addition, alternative treatment modalities, other than cytotoxic chemotherapy, are needed for pulmonary adenocarcinoma patients without druggable molecular alterations. To solve these issues, other strategies for pulmonary adenocarcinoma need to be established, and recently cancer immunotherapy has emerged as a promising therapeutic strategy.…”
mentioning
confidence: 99%
“…Randomized phase 3 studies have shown better progression-free survival (PFS) and responses with gefitinib or erlotinib than platinum-based chemotherapy for NSCLC harboring EGFR mutations (3)(4)(5)(6)(7)(8). However, most of NSCLC patients treated with EGFR tyrosine kinase inhibitors (TKI) eventually develop acquired resistance, necessitating alternative treatment strategies (9,10). Approximately half of patients have a secondary EGFR mutation in exon 20 (T790M), which is proposed to cause resistance by interfering with binding of TKIs or by increasing the affinity for ATP (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…MET amplification (5%) that results in high-level Met receptor expression can enhance heterodimerization with her3 (ErbB3) to activate downstream pi3k-Akt signalling despite inhibition of egfr activation 15 . This bypass mechanism can also result from increased production of hepatocyte growth factor, the ligand for Met 16 . As with MET, her2 (ErbB2) amplification (8%-13%) leads to parallel signalling that bypasses the effects of egfr tkis 17 .…”
Section: Mechanisms Of Acquired Resistance To Egfr Tki Therapymentioning
confidence: 99%